"A Circuit Tour of the Globe": "Hiawatha" and the Double-Stake of Imperial Pop. Issue 1 (18th February 2019) - SCHENKER, FREDERICK J.
Abstract: Between 1903 and 1904, the two-step "Hiawatha" spread rapidly throughout much of the colonial world. The travels of "Hiawatha" reveal both what Stuart Hall calls the "double-stake" of popular culture as well as what Amy Kaplan describes as the "anarchic" nature of empire: through its circulation and repeated hearings, "Hiawatha" became both a kind of colonizing force and also a medium that disturbed ideas about racial hierarchies and nationhood that served to justify colonial rule. By charting the global movement of "Hiawatha, " I show how the song became both a colonial force and also a medium for expressions that challenged imperial logic. The tune exhibited imperial tendencies: it saturated soundscapes and, as part of an emerging form of new musical commodities, coaxed listeners into recognizing their shifting status from auditors to consumers. Through its Native American subject matter, the song also helped to perpetuate ideas of evolutionary racial science that served to justify the violence of imperialism. The very qualities that made "Hiawatha" a colonizing song, though, especially its repetitious ubiquity, also increased the complexity of its meaning as it circuited the globe, leading some listeners to hear an accumulation of meanings that seemed to exceed the forms of US imperial pop.